Ab initio study of the role of defects on the magnetic response and the structural, electronic and hyperfine properties of ZnFe2O4 - Melo Quintero, Jhon Jaither (2019)
In this work the effects of defects (oxygen vacancies, cationic inversion) on the structural, electronic and the magnetic response of the spinel ZnFe2O4 (ZFO) are studied by using a density functional theory (DFT) based ab initio method (the Full-Potential Linearized Augmented Plane Waves plus Local Orbitals, LAPW+lo) on the framework of the Generalized Gradient Approximation plus U (GGA+U) level. The changes induced by the defects in the hyperfine interactions at the Fe sites of the structure are also presented. In order to discuss the magnetic ordering and the electronic structure of the system we considered different spin arrangements. We found that, similar to the normal and pristine case, reduced and partially inverted ZFO presents an energy landscape characterized by a large number of metastable states. Our calculations successfully describe the hyperfine properties (isomer shift, magnetic hyperfine field and quadrupole splitting) at the Fe sites that are seen by Mössbauer Spectrocopy (MS) at 4 and 300 K, enabling us to characterize the local structure around Fe atoms. Our LAPW+lo predictions also demonstrate the relevance of both oxygen vacancies and antisites (cationic inversion) in the formation of local ferromagnetic coupling between Fe ions, giving rise to a ferrimagnetic ordering in an otherwise antiferromagnetic compound. This results support conclusions based in experimental results obtained in x-ray magnetic circular dichroism and magnetization measurements performed on zinc ferrites with different cation distributions and oxygen vacancy concentrations reported in the literature.